Attitudes of Students of Physical Education at the University of Jadara towards Distance Education - Alnuman, Natheir Faisal Mansour; bataineh, Ra’ed rafe’ ali; kharashqah, Ruba fakhri; alshorman, Salwa adnan; Alqatami, Haya Mohammad; Aljarrah, Shefa’ Salah; almehsen, Tharwat sayel (International Journal of Membrane Science and Technology, 2023)
The study aimed to identify the attitudes of the students of the Department of Physical Education at the University of Jadara towards distance education. The program was conducted through a questionnaire consisting of (18) items that dealt with three axes of evaluation, capabilities, and educational competencies. 0.05) in favor of female students for the evaluation axis, while there are no significant differences between the two axes of educational potential and competencies